A broad spectrum Shigella vaccine based on VirG53 – 353 multiepitope region produced in a cell-free system - Girmay Desalegn; Charlotte Abrahamson; K. Ross Turbyfill; Lucy Pill-Pepe; Leslie Bautista; Chitradevi S. Tamilselvi; Dylan Dunn; Neeraj Kapoor; Barbara Sullinger; Matheo Herrera; Edwin V. Oaks; Jeff Fairman; et al. (npj Vaccines)
Abstract Dysentery caused by Shigella species remains a major health threat to children in low- and middle-income countries. There is no vaccine available. The most advanced candidates, i.e., O-polysaccharide (OPS)-based conjugates, have limited coverage—only against the immunizing serotype. Vaccines based on Shigella conserved proteins are sought for their simplicity and capacity to prevent disease caused by multiple serotypes. We previously reported the broad protective capacity of VirGα, a conserved surface-exposed domain of Shigella virulence factor. Seeking to refine the vaccine antigenic target and achieve scalable manufacturing compatible with Good Manufacturing Practices, we mapped linear B-cell epitopes spanning the entire VirG protein sequence by probing the immune reactivity of 10-mer peptides (overlapping 4–8 aa) with sera from Shigella-infected rhesus monkeys. The surface-exposed VirG53 – 353 subregion of the passenger α-domain demonstrated the highest and strongest immunoreactivity. VirG53 – 353 was produced efficiently at a large scale (>150 mg/L) using cell-free protein synthesis. When administered to mice intramuscularly, VirG53 – 353 elicited robust antibody responses and conferred high levels of protection against the three most prevalent Shigella serotypes (S. flexneri 2a, 3a, and S. sonnei). VirG53 – 353 evoked the production of Th2-type cytokines by spleen cells from vaccinated mice. A new universal Shigella vaccine based on VirG53 – 353 meets the World Health Organization’s preferred product specifications. The target antigen refinement and production improvement described here will facilitate the first-in-human studies.